2014
DOI: 10.1002/asi.23091
|View full text |Cite
|
Sign up to set email alerts
|

Historians' use of digital archival collections: The web, historical scholarship, and archival research

Abstract: This article reports a research study about historians' experiences using digital archival collections for research articles that they published in the American Historical Review. We contacted these authors to ask about their research processes, with regard to digital archival collections, and their perceptions of the usefulness of digital archival collections to historical research. This study presents a realistic portrayal of the “uses” and “impacts” of digital primary sources from the perspectives of histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 38 publications
2
41
1
1
Order By: Relevance
“…They saw drawbacks and benefits in technology: drawbacks are mentioned in connection to poor quality of images, lack of diversity, non-searchability; benefits mainly in easing searching and access, saving time, and having items universally available. This, and other studies, show an increasing reliance on general web search engines, to find resources, rather than archive-specific systems [9,26,33,34,35]. Sinn and Soares (2014) therefore conclude that digital project developers should try to make their entire collection database indexable by search engines [9].…”
Section: Literature Review and Synthesismentioning
confidence: 81%
See 3 more Smart Citations
“…They saw drawbacks and benefits in technology: drawbacks are mentioned in connection to poor quality of images, lack of diversity, non-searchability; benefits mainly in easing searching and access, saving time, and having items universally available. This, and other studies, show an increasing reliance on general web search engines, to find resources, rather than archive-specific systems [9,26,33,34,35]. Sinn and Soares (2014) therefore conclude that digital project developers should try to make their entire collection database indexable by search engines [9].…”
Section: Literature Review and Synthesismentioning
confidence: 81%
“…These patterns appear not to have changed much in a decade, as Sinn & Soares noted that historians show similar information behaviors with digital collections [9]. Chassanoff claimed that it is not possible to identify from the literature which would be historians' preferred search and retrieval strategies in archival settings [8], However, she also found that historians' preferred ways of locating primary sources are finding aids, archivists and citation linking; the methods deemed most useful are not necessarily the most frequently used, due to experience, availability, etc.…”
Section: Literature Review and Synthesismentioning
confidence: 98%
See 2 more Smart Citations
“…A part of the question of the usefulness of information has been discussed extensively in information science research from the perspectives of information needs (Savolainen, 2017) and relevance (Saracevic, 2016) even if there is much less research on the topic in the context of use and perceived usefulness (for exceptions e.g. Madden et al, 2007;Soomai et al, 2011;Sinn & Soares, 2014) than assumptions and expressions of needs and the relevance of retrieved information. Usefulness and relevance are only a part of the broader question of the value or worth of information, but for the mainstream information science research aiming at understanding and facilitating information work, it is one of the key aspects of the issue (e.g.…”
Section: Development-led Archaeologymentioning
confidence: 99%